Coaching as A Strategy for Empowering Communication Skills in The Educational Context - Jokky Jokky; Julia Surya (International Journal of Educational Management and Innovation, 2022)
The ranking of education in Indonesia, which is quite far behind compared to other countries, shows several problem factors found by educators and students. Several facts were found by researchers when conducting preliminary research that communication skills between educators and students were less developed. Therefore, some strategies were developed to improve communication skills between teachers and students, one of which is using the coaching method. This study aims to describe the implementation of coaching as a strategy for empowering communication skills in the educational context. The method used in this research is the descriptive qualitative method. The results show that coaching can be a strategy for empowering communication skills in the educational context, especially between educators and students. By comparing with previous studies, the novelty element in this research is the coaching method implemented on students with different levels of education, namely in primary and secondary schools,which educators carry out with different qualifications.